COMPARISON OF TREMOR RELATED ADVERSE DRUG REACTION BETWEEN INTRAVENOUS AMINOPHYLLINE AND NEBULIZED SALBUTAMOL FOR ASTHMA EXACERBATION TREATMENT - Amelia Lorensia; Nur Annisa Yuliana (Jurnal Insan Farmasi Indonesia, 2021)
The Department of Health estimates that asthma including 10 major causes of morbidity and mortality in the hospital. Asthma is a chronic respiratory disease that is becoming a serious health problem in many countries around the world. Drugs used in the treatment of asthma exacerbations is salbutamol and aminophylline. Drugs such as salbutamol and aminophylline can cause ADR (Adverse Drug Reaction) in the form of tremor with a sign involuntary shaking part of the hand. This research was conducted at the RSAL Dr. Oepomo to sample Aminofilin and in hospitals Seowandi to sample Salbutamol. The method used was quasi experimental. This study was conducted to compare the incidence of tremor in both asthma drug that is often used for the treatment of asthma such as Salbutamol and Aminofilin. The results of this study indicate there are differences in the incidence rate of ADR-related tremor between salbutamol and Aminofilin. Knowing the difference in incidence rate of tremor between aminophylline and salbutamol can assist in the selection of treatment which safer to avoid the effects of tremors that can occur from the use of of drugs asthma exacerbations.